Indigenous Intellectuals in Contemporary Ecuador: Encounters with "Seven Erroneous Theses about Latin America". (March 2018) - Fernández, Blanca Soledad
The indigenous intellectuals who were part of the foundation of the Ecuadorean indigenous movement of the 1980s contributed to the theoretical and political grounding of the concept of the plurinational state that is now recognized in the country's new constitution. This concept constitutes a critique of the idea of nationhood that developed in Latin America throughout the twentieth century. A comparative reading of these intellectuals' work on the occasion of the fiftieth anniversary of the publication of Rodolfo Stavenhagen's "Seven Erroneous Theses about Latin America" reveals two themes: colonial continuity and historical continuity. Both can be seen as a "settling of scores" with colonialism understood both as a historical period and as an analytical term for understanding the social reality of Latin America. Los intelectuales indígenas que formaron parte de la fundación del movimiento indígena ecuatoriano hacia la década de 1980 contribuyeron a la fundamentación teórica y política de la noción de Estado plurinacional, hoy reconocida por la nueva constitución del Ecuador. Sus principales antecedentes se encuentran en la elaboración de una crítica a la idea de nación tributaria de la corriente de pensamiento que se forjó en Nuestramérica a lo largo del siglo XX. Una lectura comparada de las obras escritas por estos intelectuales indígenas ecuatorianos en el marco de la conmemoración de los cincuenta años de la publicación de las "Siete tesis equivocadas sobre América Latina, " de Rodolfo Stavenhagen, revela dos elementos que aparecen reiteradamente a lo largo de su producción escritural: la idea de "continuidad colonial" y la idea de "continuidad histórica." Ambas nociones remiten a un tema específico que se relaciona con cierto "ajuste de cuentas" con el colonialismo en tanto hecho histórico y en tanto categoría para el análisis de la realidad social en América Latina.